Mangrove endophytic fungi: Biocontrol potential against Rhizoctonia solani and biofertilizers for fragrant rice cultivation - Manjula Muthu Narayanan; Faizah Metali; Pooja Shivanand; Norhayati Ahmad (Heliyon, 2024)
The mangrove ecosystem has emerged as a fascinating source for exploring novel bioresources which have multiple applications in modern agriculture. This study evaluates the potential applications of mangrove endophytic fungi (MEF), such as biocontrol agents against Rhizoctonia solani and as biofertilizers for improving the yield of fragrant rice variety Malaysian Rice Quality 76 (MRQ76). Through the antagonism assays, it is observed that among the 14 MEF studied, 4 fungal isolates (Colletotrichum sp. MEFN02, Aspergillus sp. MEFN06, Annulohypoxylon sp. MEFX02 and Aspergillus sp. MEFX10) exhibited promising antagonistic effect against the pathogen R. solani compared to the chemical fungicide (Benomyl). These isolates also revealed significant production of enzymes, phytochemicals, indoleacetic acid (40.96 mg/mL) and ammonia (32.54 mg/mL) and displayed tolerance to salt and temperature stress up to 2000 mM and >40 °C respectively. Furthermore, employing the germination and pathogenicity test, inoculation of these endophytes showed lower percentage of disease severity index (DSI%) against R. solani, ranging from (24 %–46 %) in MRQ76 rice seedlings. The in-vivo experiments of soil and seed inoculation methods conducted under greenhouse conditions revealed that these endophytes enhanced plant growth (8–15 % increase) and increased crop yield (≥50 %) in comparison to control treatments. The current findings provide valuable insights into eco-friendly, cost-effective and sustainable alternatives for addressing R. solani infection and improving the agronomic performance of the fragrant rice cultivar MRQ76, contributing to food security.